Penerapan Media Pembelajaran Daring Terhadap Minat Belajar Mahasiswa - Interdiana Candra Sari, Ani; Rasam, Fadli; Karlina, Elin (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
This study is entitled The Application of Online Learning Media to Students' Learning Interests during the Covid-19 Pandemic. The purpose of this study was to determine the Application of Online Learning Media to Student Learning Interests during the Covid-19 Pandemic Period of Economic Education Study Program, Indraprasta University, PGRI. The method to be used is a Completely Randomized Design experiment that does not use control and comparative classes. Researchers will use two classes, class A as experimental class 1 with zoom learning media and class B as experiment class 2 with Google Classroom learning media, from the two methods used by researchers will see and compare student learning outcomes and how student interest in learning with both media the learning. Based on the research results, it can be concluded that there is an influence of zoom learning media on student learning interest. There is an effect of GC learning media on student interest in learning. There is no difference in interest in learning through zoom and GC learning media.